2014
DOI: 10.1111/hpb.12078
|View full text |Cite
|
Sign up to set email alerts
|

2564 resected periampullary adenocarcinomas at a single institution: trends over three decades

Abstract: There are significant differences among PACs in longterm survival following PD. Although the numbers of patients undergoing safe resection have increased, overall longterm outcomes have not improved significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
193
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(213 citation statements)
references
References 35 publications
15
193
1
4
Order By: Relevance
“…The most frequent complication of periampullary surgery is pancreatic fistula, which is reported at variable rates in the literature, ranging from 9% and 12% to 29% (13,24,26,28). In the present study, the rate was 23.9%, with no statistically significant betweengroup differences.…”
contrasting
confidence: 42%
“…The most frequent complication of periampullary surgery is pancreatic fistula, which is reported at variable rates in the literature, ranging from 9% and 12% to 29% (13,24,26,28). In the present study, the rate was 23.9%, with no statistically significant betweengroup differences.…”
contrasting
confidence: 42%
“…Additionally, the local recurrence of the tumour is also rare when compared to local excision even in small ampullary tumours [19] . While overall morbidity of 31.2% and perioperative 90 days mortality of 4.7% in our series well correspond with the published data, and the rate of clinically significant pancreatic fistulas (ISGPF grades B and C) of 8.3% does not exceed the rates reported by other groups [5,20], we reckon this approach rational.…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrate improved pathologic findings and survival associated with the administration of neoadjuvant therapy between operations. Large series of resected pancreas cancer have reported that the morbidity and mortality are approximately 33-53% and 2-4.4%, respectively (20)(21)(22)(23)(24)(25)(26)(27). Our study demonstrates that the overall morbidity and mortality rates are similar between the re-explored group and R2 resection patients (P=0.605 and P=0.35, respectively).…”
Section: Discussionsupporting
confidence: 58%